(untitled) (AYUSHDHARA, 2024)
Nasya is one among the five important Panchkarma procedures. The unit of measurement used to explain the Nasya dosage is Bindu. One Bindu is typically understood to be one drop (0.05ml) in Ayurvedic practice, while Acharayas defines Bindu as one Shana, which is ten times the commonly used dose. This study addresses the traditional understanding of Bindu and how it should be standardized for various Nasya Kalpanas. A few publications previously published discussed the standardization of Bindu Pramana for Sneha Kalpana of Nasya. However, our classical books do not provide a standard Pramana for another Nasya Kalpana, such as Ksheer, Swarasa and Kwath Kalpana. Thus, for these Kalpanas of Nasya we are attempting to standardize Bindu Pramana of Nasya. Method and Material: 40 volunteers aged between 18 to 40 years were considered and in each group for Ksheer, Swarasa and Kwatha Kalpana of Nasya, irrespective of sex and age were selected for the study. Group A: 40 people were asked to dip their fingers up to 2nd interphalangeal joint in cow milk and all drops dribbled were considered 1 Bindu. Group B: 40 people were asked to dip their fingers up to 2nd interphalangeal joint in Tulsi Patra Swaras and all drops dribbled were considered 1 Bindu. Group C: 40 people were asked to dip their fingers up to 2nd interphalangeal joint in Dashmoola kwath and all drops dribbled were considered 1 Bindu. Conclusion – The study showed variations in dose of Bindu as per the different Kalpanas of Dravya used for Nasya.